2020
DOI: 10.3399/bjgpopen20x101069
|View full text |Cite
|
Sign up to set email alerts
|

Should chloroquine and hydroxychloroquine be used to treat COVID-19? A rapid review

Abstract: Background: On the 11 March 2020, the World Health Organization (WHO) declared that COVID-19 was a pandemic. To date, there are no medical treatments for COVID-19 with proven effectiveness. Novel treatments and/or vaccines will take time to be developed and distributed to patients. In light of this, there has been growing interest in the use of existing medications, such as chloroquine (CQ) and hydroxychloroquine (HCQ), as potential treatments of this disease.Aim: To establish the current evidence for the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 29 publications
0
89
0
4
Order By: Relevance
“…This is in agreement with the other authors with similar findings of lack of literature in this regard. 28,29,30,46 The earliest nonempirical evidence came from China in form of report letter in which more than 100 patients with COVID pneumonia showed clinical improvement and changes in image findings on chloroquine administration. 43 It is pertinent to note that this letter was the brief report of ongoing many trials in various locations in China, neither it mentioned any specific data regarding interventions, study design, study population and outcome measures, nor any adverse events were discussed.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the other authors with similar findings of lack of literature in this regard. 28,29,30,46 The earliest nonempirical evidence came from China in form of report letter in which more than 100 patients with COVID pneumonia showed clinical improvement and changes in image findings on chloroquine administration. 43 It is pertinent to note that this letter was the brief report of ongoing many trials in various locations in China, neither it mentioned any specific data regarding interventions, study design, study population and outcome measures, nor any adverse events were discussed.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently suggested that chloroquine (CQ) and hydroxychloroquine (HCQ) may be useful in the treatment of COVID-19, but presently there is inadequate evidence to support their safe and effective treatment of COVID-19 [33]. There is emerging evidence suggesting that CQ and HCQ may directly impact cornavirus attachment to respiratory cells [34], but there is also interesting potential modes of action for these drugs with respect to respiratory conditions associated with COVID-19.…”
Section: Chloroquine/hydroxychloroquine Treatmentsmentioning
confidence: 99%
“…In fact, only preventive and supportive therapies directed to prevent complications of the disease and organ damage are available. Although antimalarial drugs chloroquine and hydroxychloroquine are used in some countries for the treatment of this disease, at present there is not sufficient evidence to determine whether they are effective treatments for COVID-19 [5].…”
Section: Introductionmentioning
confidence: 99%